PERANCANGAN DAN PENGEMBANGAN APLIKASI WEB PELAPORAN KAMPUS DI UNIVERSITAS NEGERI MEDAN DENGAN INTEGRASI CHATBOT - Freyro Dobry Sianipar; Muhammad Hidayatul Arifin; Windy Aulia; Muhammad Haikal Al Majid; Adidtya Perdana (LPPM Universitas Dhyana Pura, 2025)
Conventional reporting systems in the campus environment often produce reports that are not well documented, which causes the handling process to be slow and unclear. This is the problem underlying this research. The purpose of this research is to create and develop a campus reporting web application integrated with a chatbot to increase transparency, speed, and efficiency in the delivery and handling of reports. The method used is Research and Development (R&D) with the Waterfall development model, including the stages of needs analysis, system design, implementation, testing, and evaluation. This application development uses PHP programming language for the backend, MySQL as the database, and Tailwind CSS and JavaScript for the user interface. Chatbase is used to integrate a chatbot to answer automated questions about the reporting process. The results showed that the developed application was able to facilitate the reporting process systematically through the input form feature, user authentication, and a dashboard that monitors the status of the report, which facilitates the management of reports by the campus. In addition, the chatbot feature helps answer user questions quickly and precisely, increasing user interaction and satisfaction. The conclusion of the study shows that the use of a reporting web application with a chatbot can improve the flow of reports, accelerate handling responses, and increase transparency and documentation in report management in the campus environment.